Ceruletide increases dose dependently both jejunal motor activity and threshold and tolerance to experimentally induced pain in healthy man. Issue 5 (May 1984) - Stacher, G; Steinringer, H; Schmierer, G; Schneider, C; Winklehner, S; Mittelbach, G; De Paolis, C; Praga, C
Abstract : The effects of ceruletide on jejunal motility and experimentally induced pain were studied in 16 healthy men, who participated each in four experiments and received in random double blind fashion 5, 10, or 20 micrograms ceruletide intramuscularly or placebo. Jejunal pressures were recorded by three perfused catheters with orifices between 10 and 20 cm aboral of the ligament of Treitz. Ceruletide dose dependently diminished phase I and increased phase II type activity and tended to reduce the number, but not the duration, of activity fronts. The number and amplitude of contractions as well as the area under the curve increased significantly and dose dependently as did threshold and tolerance to electrically and threshold to thermally induced pain. Only mild sedative and other side effects occurred.